Synthesis and properties of La-Fe-Si/La-Co magnetocaloric composites - Wu, Yu-Cai (2023)
LaFe11.8Si1.2/16wt%La65Co35 samples were prepared by spark plasma sintering (SPS) and subsequent annealing. The La65Co35 binder increased the desired 1:13 phase content in these samples during annealing at 1323 K. Interestingly, the α-Fe phase formed between the LaFe11.8Si1.2 particles and the La65Co35 binder and then disappeared as the annealing time extended. The sample annealed for 0.5 h had a distinct core-shell structure with Co in the shell, a desirable table-like (−∆SM)−T curve was obtained and its RC (153 J·kg−1) was 107% higher compared to the sample before annealing. The diffusion of Co from La3Co to the 1:13 phase was hampered by the growth of La5Si3 phase. Relatively large (−∆SM)max of 8.51 J·kg−1·K−1 (Δμ0H=2 T) and (σbc)max of 374 MPa for the sample annealed for 24 h were obtained. These results indicated that the method combining SPS and diffusion annealing is promising to prepare La-Fe-Si based magnetocaloric composites with good properties.